Dampak Implementasi Sistem Informasi Akuntansi atas Kualitas Data Keuangan UMKM Saat Pandemi di Bandar Lampung - Akadiati, Victoria Ari Palma; Sinaga, Imelda; Sumiyati, Lydia (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p12, 2022)
The implementation of SIA (Accounting Information System) has led to modern accounting departments in organizations such as MSMEs for financial management. However, most MSME owners do not realize the importance of this. The purpose of this study is to re-investigate the impact of the implementation of AIS on the quality of MSME financial data in Bandarlampung. The study used quantitative data using a questionnaire on the multiple linear regression method. The population used was 417 MSMEs and the sample used was 200 MSMEs in Bandar Lampung. The results showed that the information system application variables, input variables in the accounting information system application, and security variables from the AIS application had a significant positive effect on the quality of financial data. This means that the implementation of AIS in MSMEs must be maintained and the use of information technology increased in accordance to the improve the quality of MSME financial data for its users. This is because the existence of technology such as AIS can make it easier for users to make decisions from evaluating financial performance for the sustainability of MSME businesses. Keywords: AIS; MSME; Data; Financial.